2009
DOI: 10.1111/j.1742-1241.2009.02008.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of age and disease on survival of chronic lymphocytic leukaemia patients by a new method

Abstract: Chronic lymphocytic leukaemia had a more unfavourable presentation and a more severe clinical course in the younger patients. Our method of evaluating the negative impact of disease on expected survival reveals that their survival also is significantly more affected than that of older patients. We suggest calculating the loss of expected survival as a new criterion for assessing disease impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The proportion of CLL patients with Rai stage 2 or higher is larger in patients younger than 65 years and the loss of life expectancy in younger patients is more than twice as high as in older individuals. 5 Amongst other prognostic factors, lymphocyte doubling time (LDT) in untreated patients deserves special attention. Lymphocyte doubling time longer than 12 months is usually associated with a mild course of CLL; however, the shorter the LDT, the more aggressive is the phenotype of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of CLL patients with Rai stage 2 or higher is larger in patients younger than 65 years and the loss of life expectancy in younger patients is more than twice as high as in older individuals. 5 Amongst other prognostic factors, lymphocyte doubling time (LDT) in untreated patients deserves special attention. Lymphocyte doubling time longer than 12 months is usually associated with a mild course of CLL; however, the shorter the LDT, the more aggressive is the phenotype of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, CLL is clinically heterogeneous and, although some investigators have found no difference in outcome between younger and older patients, others have reported that CLL has a bigger impact on life expectancy in younger patients, in whom it is more aggressive (CLL may be life-threatening in ϳ 60% of younger patients). [5][6][7][8] The frequency and duration of treatment responses in CLL have both improved substantially in recent years. Complete response (CR) rates obtained in controlled studies have increased from Ͻ 5% with chlorambucil to 20% with fludarabine or CHOP (cyclophosphamide, hydroxydaunorubicin, oncovin, and prednisone/ prednisolone), 30% with the fludarabine-cyclophosphamide combination (FC), and 44% with FC plus rituximab, an anti-CD20 antibody (FCR).…”
mentioning
confidence: 99%